(untitled) (Research, Society and Development, 2019)
Geographical Indications can be considered as strategies that contribute to the process of rural development, since they can add value to products or services that have their own characteristics linked to the territory where they are inserted. The objective of this study was to evaluate the influence of Geographical Indications on socioeconomic benefits and to identify the types of institutions that contributed to the process of registration and maintenance of the Geographical Indication in the country. The methodological procedures adopted are of a qualitative nature, through the utilization of bibliographic and documentary revision techniques. Through the results achieved, it was verified that the consolidation of Geographical Indications in the country can contribute to the Rural Development process due to a series of socioeconomic benefits that can be achieved by rural communities, such as the generation of employment and income, as well as such as the appreciation of the local culture. In addition, the importance of the involvement and partnerships of various types of institutions for the elaboration of the process and maintenance of Geographical Indication for a given territory is also highlighted.